MODERN STAGE TECHNOLOGY: मंच की आधुनिक तकनीक - Shah, Rajeshwari (International Journal of Research -GRANTHAALAYAH, 2015)
The stage has originated since the dance began. Dances are observers whenever they occur. In the second chapter of the Natya Shastra, the Rang Mandap has been created. In which Jyestha (big), Madhyam (elder than student), Kanisht (most students). In that period, a good description of the stage arrangement is found in which the hall for the seating of the stage, the stage ie the background, and then the color of the greenery room is also not found. A description of two platforms is also found on the stage. So that two different scenes Can be seen together. मंच का उद्भव तभी से प्रारंभ हुआ जब से नृत्य प्रारंभ हुआ। नृत्य जब भी होता है प्रेक्षक होते ही है। नाट्य शास्त्र के दूसरे अध्याय में रंग मंडप के प्रकार बनाए गए हैं। जिसमें ज्येष्ठ (बड़ा), मध्यम (ज्येष्ठ से छोटा), कनिष्ट (सबसे छोटा)। उस काल में मंच व्यवस्था का उत्तम विवरण मिलता है जिसमें दर्षकों के बैठने के लिए हाॅल, स्टेज अर्थात् रंगभूमि उसके बाद नैपत्थ्य अर्थात ग्रीन रूम का भी वर्णन मिलता है। स्टेज पर दो प्लेटफार्म का भी वर्णन मिलता है। जिससे अलग-अलग दो दृष्य एक साथ देखे जा सकें।